RETRACTED: Physical exercise and psychological health of rural left-behind children: An experiment from China - Qijie, Jiang; Yin, Li; Liping, Li (Frontiers in Psychology, 2022)
Background How to promote the health (especially mental health) growth of left-behind children has become a hot social issue. Physical exercise is usually considered as a positive role in improving the physical and mental health of children, which can be considered to be integrated into the living environment of left-behind children. Objective To discuss the changes of left-behind children in psychological health before and after the exercise-based intervention, thus providing a practical approach to improve the psychological growth of this disadvantaged group. Methods An exercise-based social intervention experiment was designed and conducted in a township middle school in China, and 200 left-behind children with relatively low psychological health participated in the experiment. Results Physical exercise had positive effects on rural left-behind children’s sense of hope, self-esteem, self-efficiency, and self-concept, and it seems that the positive effects are durative due to the optimization of living environment. There was no significant difference in the psychological promotion effect of different programs (football and table tennis) on left-behind children. Hope, self-esteem, and self-efficiency significantly mediated the relationship between physical exercise and self-concept of left-behind children. Conclusion Physical exercise contributes to promoting the development of rural left-behind children’s positive psychology such as hope, self-esteem, self-efficiency, and thus relieving the negative psychology caused by long-term parental-child separation and improving self-concept.